2007
DOI: 10.1007/s10493-007-9075-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Bradysia matogrossensis (Diptera: Sciaridae) in mushroom cultivation with predatory mites

Abstract: Larvae of Sciaridae flies (Diptera) cause considerable damage to the mushroom Agaricus blazei (Murrill) ss. Heinemann in Brazil. Brazilian growers have had considerable difficulties in controlling this pest. The objective of this work was to test the effect of the predatory Laelapidae mite Stratiolaelaps scimitus (Womersley) as a control agent of Bradysia matogrossensis (Lane) in cultures of A. blazei. The work corresponded to an evaluation of the efficiency of that predator when released in boxes containing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Cabrera et al and Gulati [45][46][47] reported that T. myceliophagus, T. confuses and T. floreicolus occur in thousands on mushroom body and the affected tissue becomes reddish, while base and stalk turn brown in colour. Accordingly Pygmephous sp.…”
Section: Effect Of Infestation On Biochemical Composition Of Pluerotumentioning
confidence: 99%
“…Cabrera et al and Gulati [45][46][47] reported that T. myceliophagus, T. confuses and T. floreicolus occur in thousands on mushroom body and the affected tissue becomes reddish, while base and stalk turn brown in colour. Accordingly Pygmephous sp.…”
Section: Effect Of Infestation On Biochemical Composition Of Pluerotumentioning
confidence: 99%
“…are more successful in minimizing pest damage to mushrooms and maximizing the yield [14]. Pesticides (permetrin, perefosmetil, anometrin, forbecide and dichlorvos) are applied [15], but due to growing ecological and health concerns, biocontrol methods are being developed against pest [16]. In mushroom bed, incorporation of diazinon in compost at filing time and dicofol (0.1%) as prophyletic measure against flies is recommended in the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Among the groups of Gamasina found in this study, it seems worthy to dedicate special emphasis to the laelapid mites, given their demonstrated potential and actual use for the control of soil insects and mites as well as of hematophagous mites (FREIRE et al, 2007;CASTILHO et al, 2009;LESNA et al, 2009LESNA et al, , 2012 …”
Section: Final Remarksmentioning
confidence: 90%
“…For this reason, members of that order have been studied as predators of edaphic pests (INSERRA;DAVIS, 1983;WALTER, 1986, LESNA et al, 2000ALI;DUNE;BRENNAN, 1997;FREIRE et al, 2007). In a survey conducted in Switzerland by Maurer et al (1993), Androlaelaps casalis (Berlese) (Mesostigmata: Laelapidae) was reported in poultry houses.…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation